استخدام لوحات السيطرة الإحصائية ومقدرة العمليات الإنتاجية في تطوير اعمال السيطرة النوعية في معامل القابلوات في شركة أور العامة للصناعات الهندسية (University of Thi-Qar Journal for Engineering Sciences, 2011)
This paper investigates the use of statistical control techniques such as (statistical control charts and process capability) in quality control of the electrical wires and cables which were produced in Ur Company (Cable factories) and in order to evaluate the performance of the manufacturing machines. Two types of manufacturing processes were selected namely (drawing and insulation) by testing diameter, max. tensile strength, elongation, and electrical resistance of wires, and testing of nominal thickness, strength, and elongation of insulation and sheathing of cables, for evaluating of quality control and process capability by using control charts namely (Average-Range) chart and process capability calculations and statistical analysis based on histogram technique. The results showed that some of machines are unable to satisfy the specification tolerances due to wide differences in the resulted values of the statistical parameter. Therefore, it is important to carry out the total maintenance for these machines, and increase the quality control activities such as testing the raw materials by chemical analysis.